Dog blogs as ventriloquism: Authentication of the human voice. (June 2015) - Leppänen, Sirpa
Abstract: This paper looks at personal blogging by dog owners in an international, English language blogsite in which dog owners from around the world report and reflect upon their dogs and their lives with dogs, and do so by using the dog׳s voice. It approaches dog blogs as an example of the strategic use of pervasive but contentious anthropomorphic western discourses about animals and discusses how dog bloggers use anthropomorphism as a discursive means for crafting and collectively ratifying authenticity in a translocal, interest-driven and informal social media context in which traditional territorial and demographic parameters of authenticity are not easily available or relevant. More specifically, the paper shows how the discursive means for authentication in dog blogging entail deliberate acts of ventriloquism and stylization. It analyses the ways in which these function to authenticate bloggers socially and morally as legitimate participants in dog blogging and as particular kinds of persons. Further, it discusses how a range of norms associated with blogging, on the one hand, and historically specific discourses about humans and companion animals, on the other hand, are recontextualized for the purposes of the socio-cultural niche in question. Particular attention is paid to how linguistic and discursive features associated with diary writing, as well as to how western discourses of dogs and animals are mobilized in the establishment, maintenance and regulation of the global practice about dogs in a way that is highly indexical of idealized, classed gender. Highlights: The global practice of blogging about dogs is an example of the significance of authentication in social media practice. In informal, interest-based social media practices authentication requires consent, uptake and regulation of a particular discursive orientation. In blogging about dogs discursive authentication involves stylization and ventriloquism. In stylization and ventriloquism, bloggers mobilize linguistic and discursive features associated with diary writing and western discourses of dogs and the dog–human relationship. Dog blogging is highly indexical of idealized, classed gender.